GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PENYAKIT ANEMIA DALAM KEHAMILAN DI DESA PERCUT KABUPATEN DELI SERDANG - Rosa Zorayatamin Damanik (Universitas Islam Sumatear Utara, 2023)
Anemia is the most common nutritional problem in Indonesia. In pregnant women, anemia can increase the number of complications in childbirth and pregnancy. The purpose of this study is to figuring out pregnant women knowledge about anemia in pregnancy. The methods of this study is descriptive study. The measurement used by this study was questionnaires. The population represents all the pregnant women in the village of Percut district Deli Serdang with study sample are 72 respondents. The results of this study, there are 73,6% pregnant women having good knowledge of the understanding of anemia ,66,7% pregnant women having good knowledge of the causes of anemia, 62,5% pregnant women having good knowledge of the symptoms of anemia are, 70,8% having good knowledge of the impact of anemia, and 68,1% pregnant women having a good knowledge of the prevention of anemia.